The Effect of Profitability, Good Corporate Governance, and Environmental Disclosure on Firm Value in Mining Companies Listed on The Indonesia Stock Exchange - Muhammad Alfin Yusra; Erna Sulistyowati (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The purpose of this research is to examine and analyze the influence of profitability, good corporate governance, and environmental disclosure on the firm value of mining companies listed on the Indonesia Stock Exchange. The research method utilized is descriptive research with a quantitative approach. The study population encompasses all mining companies registered on the Indonesia Stock Exchange (IDX) within the period from 2019 to 2022. In this study, a non-probability sampling technique was employed, specifically purposive sampling, resulting in a sample size of 72 from a span of 18 companies over 4 years. The variables under scrutiny include Return on Assets (ROA) as a measure of profitability, the proportion of independent board commissioners as an indicator of good corporate governance, the number of GRI disclosures as an indicator of environmental disclosure, and Tobin’s Q as a gauge of firm value. The analytical methodology and hypothesis testing were carried out using the Partial Least Square (PLS) method with SmartPLS 3.2.9 software. The PLS analysis consists of three stages: Outer Model, Inner Model, and Hypothesis Testing. The hypothesis testing results show that profitability has a significant impact on firm value, while good corporate governance and environmental disclosure do not exhibit a significant influence on firm value. These findings contribute to the understanding of how these factors interplay within the mining sector. However, this study has several limitations, including the variables used, the company's disclosures, and the limited period. Subsequent research can address these limitations and delve deeper into exploring the relationships of these variables or other variables with firm value.